Plasmodium Circumsporozoite Protein Enhances the Efficacy of Gefitinib in Lung Adenocarcinoma Cells by Inhibiting Autophagy via Proteasomal Degradation of LC3B - Lu, Xiao; Zhang, Jiao; Li, Yan-Qi; Liu, Quan-Xing; Zhou, Dong; Deng, Xu-Feng; Qiu, Yuan; Chen, Qian; Li, Man-Yuan; Liu, Xiao-Qing; Dai, Ji-Gang; Zheng, Hong (Frontiers in Cell and Developmental Biology, 2022)
Background: Almost all lung adenocarcinoma (LUAD) patients with EGFR mutant will develop resistance to EGFR-TKIs, which limit the long-term clinical application of these agents. Accumulating evidence shows one of the main reasons for resistance to EGFR-TKIs is induction of autophagy in tumor cells. Our previous study found that circumsporozoite protein (CSP) in Plasmodium can suppress autophagy in host hepatocytes. However, it is unknown whether CSP-mediated inhibition of autophagy could improve the anti-tumor effect of EGFR-TKIs. Methods: We constructed A549 and H1975 cell lines with stable overexpression of CSP (OE-CSP cells). CCK-8, Lactate Dehydrogenase (LDH), flow cytometry, and colony analysis were performed to observe the effect of CSP overexpression on cell viability, apoptosis rate, and colony formation ratio. The sensitizing effect of CSP on gefitinib was evaluated in vivo using a subcutaneous tumor model in nude mice and immunohistochemical assay. The role of CSP in regulation of autophagy was investigated by laser confocal microscopy assay and western blotting. A transcriptome sequencing assay and real-time polymerase chain reaction were used to determine the levels of mRNA for autophagy-related proteins. Cyclohexane (CHX), MG132, TAK-243, and immunoprecipitation assays were used to detect and confirm proteasomal degradation of LC3B. Results: OE-CSP A549 and H1975 cells were more sensitive to gefitinib, demonstrating significant amounts of apoptosis and decreased viability. In the OE-CSP group, autophagy was significantly inhibited, and there was a decrease in LC3B protein after exposure to gefitinib. Cell viability and colony formed ability were recovered when OE-CSP cells were exposed to rapamycin. In nude mice with xenografts of LUAD cells, inhibition of autophagy by CSP resulted in suppression of cell growth and more marked apoptosis during exposure to gefitinib. CSP promoted ubiquitin-proteasome degradation of LC3B, leading to inhibition of autophagy in LUAD cells after treatment with gefitinib. When LUAD cells were treated with ubiquitin activating enzyme inhibitor TAK-243, cell viability, apoptosis, and growth were comparable between the OE-CSP group and a control group both in vivo and in vitro. Conclusions: CSP can inhibit gefitinib-induced autophagy via proteasomal degradation of LC3B, which suggests that CSP could be used as an autophagy inhibitor to sensitize EGFR-TKIs.